Recent progress on electrochemical (bio)sensors based on aptamer-molecularly imprinted polymer dual recognition - Yixin Liu; Grace Dykstra (Sensors and Actuators Reports, 2022)
Antibodies have been the dominant receptors used to construct biosensors and bioassays owing to their intrinsically excellent antigen specificity and affinity. Despite their wide applications, antibodies suffer from many drawbacks such as high costs, poor stability, limited availability, and stringent storage conditions. Over the last three decades, aptamers and molecularly imprinted polymers (MIPs) have emerged as alternative synthetic receptors to substitute antibodies in biosensors and bioassays due to their specific conformational and binding relationships to analytes and selectivity similar to that of natural counterparts. More recently, aptamers and MIPs have been combined as a hybrid system that combines both of these synthetic recognition elements to detect various analytes such as small molecules, proteins, and viruses, utilizing their desired properties and complementing each other's limitations. Due to the overall low-cost, high sensitivity, miniaturization compatibility, and portability of electrochemical sensors, this review focuses on the recent progress of electrochemical (bio)sensors based on aptamer-MIP (AptaMIP) dual receptors since the first one reported in 2016. Three design strategies of AptaMIP-based electrochemical sensors with related works are summarized and discussed in detail, including aptamer embedded in MIP as a hybrid receptor, aptamer and MIP dual-functional areas-based microfluidic device, and MIP/Target/aptamer sandwich assay. For each strategy, sensor configurations, transducing mechanisms, strengths and limitations are discussed.